Industrial Zones and their Socio-economic Impact on Regional Development The case of Strategic Industrial Zone Nošovice - Němcová, Hana; Miksová, Blanka; Macháček, Jaroslav; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2014)
The aim of this master's thesis is to analyze and assess socio-economic impacts of strategic industrial zones on regional development. Concretely the thesis concentrates on current impacts of Strategic Industrial zone Nošovice on its closest area within Moravia-Silesia region. The theoretical part is focused on basic terms, concepts related to industrial zones and describes their positives and negatives and based on literature review discusses potential impacts. Further is briefly defined legislation related to Industrial zones establishment and also determines system of funding and support of industrial zones. The practical part first briefly describes industrial zones and its situation within Moravia-Silesia region. Further it concentrates on analysis of SIZ Nošovice and socio-economic impacts related to its establishment and current presence. Impacts are divided in three parts on economic, social and other impacts such as impacts on environment and transport infrastructure. In the end are defined proposals on further regional development in other areas. The thesis is a combination of available data, author's research and obtaining information from authorized persons related to the topic. For this evaluation are used methods such as description of statistical data, analysis and synthesis of the findings obtained.
Vedoucí práce: Blanka Miksová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2014
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2014
Způsob přístupu: Internet
Keywords: regionální studia [obor dipl. práce]; diplomové práce; master's theses